Assessing the use of harvested greenhouse runoff for managed aquifer recharge to improve groundwater status in South Portugal - Costa, Luis (2021)
Concentration of nitrates in groundwater at the Nitrate Vulnerable zone of Faro, south Portugal, reaches values as high as 300 mg/l; therefore, according to the EU Water Framework Directive, mitigation measures need to be implemented. A Managed Aquifer Recharge scheme is proposed to accelerate the dilution and natural discharge of nitrates from the system. Source water availability is estimated from rainfall intercepted at existing greenhouses. Within the highest nitrate concentration area, estimated water availability for injection in existing wells is 1.50 hm(3)/year, a significant volume which represents approximately 15% of the aquifer direct recharge. It is proposed this is recharged to the aquifer through existing large-diameter traditional wells that are no longer used for abstraction. Injection test results suggest that the likely infiltration capacity of such wells is more than sufficient to allow collection of 95% of daily rainfall events. The effect of injecting this volume in the aquifer was estimated with the support of a 3D numerical groundwater flow and transport model. Results show considerable improvement in nitrate concentrations in the study area, in certain locations decreasing up to 70 mg/l by 2027. The model results predict a decrease in the number of nitrate threshold exceedances in observation points, from 33 to 30 by 2027 and 14 to 9 by 2040. It is likely that this measure may have a positive effect on other issues identified in the area, mostly related with quantity problems and seawater intrusion. Notwithstanding, issues including landowner support, clogging, conditions of greenhouses and wells, water quality, and climate change impacts will require further consideration to develop a successful and beneficial MAR scheme.